2022
DOI: 10.15212/ijafr-2020-0150
|View full text |Cite
|
Sign up to set email alerts
|

Ruminant health research – progress to date and future prospects, with an emphasis on Irish research

Abstract: This review addresses the progress that has been made in ruminant health research over the last 60 yr, with an emphasis on Irish research. The review focuses on the economically important infectious diseases of dairy and beef cattle and of sheep, calf diseases, regulated and non-regulated infectious diseases, lameness, mastitis and parasitoses. The progress to date, current knowledge and future challenges are all addressed. Paradigm shifts have occurred in many of these diseases, the most profound of which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 304 publications
0
3
0
Order By: Relevance
“…Abortion rates were also higher in older (>3rd parity) than in younger cows (Nadri et al, 2021; Thomsen et al, 2020). But other studies (Gädicke & Monti, 2013, Norman et al, 2012, Thurmond et al, 2005, Mee, 1992, Rafati et al, 2010) found higher abortion rates in first parity cows than in older cows. Silke et al (2002) found no difference in late embryonic/early foetal mortality between heifers and cows.…”
Section: Risk Factors For Abortionmentioning
confidence: 88%
“…Abortion rates were also higher in older (>3rd parity) than in younger cows (Nadri et al, 2021; Thomsen et al, 2020). But other studies (Gädicke & Monti, 2013, Norman et al, 2012, Thurmond et al, 2005, Mee, 1992, Rafati et al, 2010) found higher abortion rates in first parity cows than in older cows. Silke et al (2002) found no difference in late embryonic/early foetal mortality between heifers and cows.…”
Section: Risk Factors For Abortionmentioning
confidence: 88%
“…S. aureus also causes severe diseases in animals such as arthritis, toxic shock syndrome, urinary tract infections, and omphalitis, an infection of the umbilicus or surrounding tissues [ 23 ]. S. aureus is also the predominant infectious pathogen causing clinical and subclinical intramammary mastitis in dairy cattle globally [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], resulting in sizable economic losses. Liebe and colleagues estimate that the US economy loses $2 billion annually due to bovine mastitis, with worldwide losses of approximately $34 billion (USD) [ 34 ].…”
Section: The Impacts Of Staph On Humans and Non-human Animalsmentioning
confidence: 99%
“…The benefits of this regime may be augmented by maternal vaccination against GI pathogens in the month before calving during colostrogenesis (Chambers et al, 2022). While studies show variable benefits of feeding pre‐ or probiotics to neonatal calves to prevent calf diarrhoea (Wang et al, 2023; Medrano‐Galarza et al, 2018), routine prophylactic or metaphylactic antimicrobial use (AMU) is no longer recommended in order to reduce the risks of antimicrobial resistance (AMR), (Mee et al, 2022).…”
Section: Neonatal Bovine Morbiditiesmentioning
confidence: 99%